Recovering Racial Positioning in "White" Women's International Thought: Lady Kathleen Simon's International Abolitionist Crusade, 1927–1955. Issue 1 (29th March 2023) - Napier, Isabelle
Abstract: The new field of history of women's international thought is part of, and gives further impetus to, the ongoing reckoning of international relations (IR) with the centrality of race and gender to the discipline. Scholars continue to recuperate a long inheritance of international thinkers concerned with race relations, colonial administration, and empire in nineteenth- and twentieth-century global political economies dependent on violent exploitation of peoples classified as inferior. This inheritance underscores that the politics of colonialism, war, humanitarianism, development, and decolonization have shaped and been shaped by processes of reinforcing and contesting racialized subject positions. Despite this, little attention has been paid to whiteness in histories of women's international thought. In this article, I recover the international thought of white British antislavery advocate and humanitarian Lady Kathleen Simon. I bring feminist and critical race scholarship to bear on Simon's writings and practice. Through her efforts to rouse a twentieth-century international abolitionist movement to emancipate those remaining enslaved in so-called backwards places, Simon played a consequential role in defending Ethiopia's occupation by fascist Italy from 1936 to 1941 and in arguing for continued European administration of Ethiopia after its liberation. In light of critiques of humanitarianism and of the role of white women in reproducing racial hierarchies in colonial and development contexts, I argue that recovery and analysis of the subject positions of historical women racialized as white is inextricable from the project of international intellectual history and from IR's continuing engagement with questions of gendered and racialized hierarchy and othering.